2019
DOI: 10.1097/prs.0000000000006008
|View full text |Cite
|
Sign up to set email alerts
|

A Matched-Pair Analysis of Prepectoral with Subpectoral Breast Reconstruction: Is There a Difference in Postoperative Complication Rate?

Abstract: Background: The development of acellular dermal matrices has revolutionized implant-based breast reconstruction. The most recent development has been the introduction of prepectoral breast reconstruction. However, concerns have been expressed related to the quality of soft-tissue coverage and infectious complications. Thus, the authors felt it prudent to perform a matched-pair analysis of clinical outcomes following prepectoral and subpectoral tissue expander placement. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
50
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 26 publications
9
50
2
1
Order By: Relevance
“…The use of postdischarge antibiotics for the patients in this study notably showed no benefit in reducing infection rate or reconstructive failure, even if β‐lactams were administered. This observation corroborates previous reports that fail to demonstrate the need for post‐discharge antibiotic prophylaxis 25,26 . Our findings are in alignment with these outcomes, implying that the preoperative and perioperative periods are the critical times when antibiotic prophylaxis with a β‐lactam is effective.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The use of postdischarge antibiotics for the patients in this study notably showed no benefit in reducing infection rate or reconstructive failure, even if β‐lactams were administered. This observation corroborates previous reports that fail to demonstrate the need for post‐discharge antibiotic prophylaxis 25,26 . Our findings are in alignment with these outcomes, implying that the preoperative and perioperative periods are the critical times when antibiotic prophylaxis with a β‐lactam is effective.…”
Section: Discussionsupporting
confidence: 92%
“…What can be concluded based on the findings of this study and a previous study by our group is that prolonged antibiotic administration beyond 24 h after surgery does not provide any benefit to patients undergoing immediate tissue expander placement. In this prior study, which included patients who underwent pre‐pectoral reconstruction (the senior author's [AM] preferred approach for implant‐based breast reconstruction) less than 24 h of antibiotic prophylaxis compared favorably to subpectoral tissue expander placement and a prolonged course of antibiotics 26 …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Susarla et al 22 highlighted an 80% increased risk of revision procedures in their hybrid ADM/sub‐pectoral one‐stage procedures, but interestingly also pointed out the patient preference for one‐stage procedures despite this. Sibitany et al, 38 Momeni et al, 39 and Antony et al 40 all supported fully pre‐pectoral ADM‐covered reconstructions (in either one or two‐stage approaches) over hybrid ADM techniques. Still, it showed much higher infections with (when results available) higher implant loss and revisions than our results, that further questions the need for ADM (Table 7).…”
Section: Discussionmentioning
confidence: 95%
“…Further, the 2007–2013 ACS-NSQIP datasets were deliberately chosen to focus our analysis on the subpectoral approach and minimize confounders. The prepectoral approach, which does not involve dissection of the pectoralis muscle, was popularized in 2014 by the advent of fat grafting and acellular dermal matrix and early promising studies such as the one published by Berna et al 18 , 19 Since the subpectoral method is much more surgically involved and has been shown to be associated with more major postoperative complications, 20 hospital LOS and morbidity from the analysis of subpectoral reconstruction can be inferred to be greater than or equal to that of device reconstruction today.…”
Section: Discussionmentioning
confidence: 99%